PSIKOEDUKASI PEMBERDAYAAN KETERLIBATAN ORANGTUA DALAM PROSES PEMBELAJARAN DEEP LEARNING SISWA - Susilo, Markus Nanang Irawan Budi; Asih, Martha Kurnia; Widyawati, Sri; Utami, Retno Ristiasih (An-Nizam, 2025)
Pedurungan State Kindergarten, Semarang is a model school for the healthy school movement by implementing the principles of nutritional, physical, immunization, environmental and mental health in the school environment. The concept of the healthy school movement is also applied to the learning approach system developed by the government, namely deep learning, which invites students to be more aware, interpret and have fun in learning. One effort to realize healthy learning outcomes, full of awareness, meaning and joy is to invite the involvement of the environment, especially parents. The problem is the lack of parental involvement which is shown in the lack of discipline in caring for and educating children at home as well as conflict between parents which has the potential to have a negative impact on children's friendship and learning situations, resulting in less than optimal learning achievement expectations. The Community Service Team from Semarang University helps provide psychoeducation related to understanding children's conditions and parental involvement as an effort to achieve learning expectations, especially increasing children's independence and interest in learning in accordance with the concept of 'deep learning'. Psychoeducation is provided through lectures and discussions. The results of this activity are shown by increasing parents' understanding of children's conditions, parenting patterns and stimulation to increase children's interest in learning so it can be concluded that this psychoeducation activity can help schools and parents implement deep learning in children.